Cardiac Arrest Induced by Anti-hypertensive and NSAIDS Drug Abuse Uses due to their Role Effect on Electrolytes and Aldosterone Levels in Hypertensive Patients with Renal Insufficiency (Indian Journal of Forensic Medicine & Toxicology, 2021)
The present study aims to investigate the role of the drugs like angiotensin converting enzyme inhibitors(ACEI), non-steroidal anti-inflammatory drugs NSAIDs and their effects in the contributions of electrolytefluctuation levels, as well as in an abuse uses. Forty four cardiac arrest subjects cases of hypertensive withrenal failure (renal insufficiency) were taken, and forty participants as a healthy control without any heartand kidney problems with same of mean age (58±5). Done in Hilla city/Iraq were enrolled in this study.Results that collected from the present study were a significant in reduction of serum aldosterone levels,with very clear raises in plasma potassium and urinary sodium levels due to the action of hypertension drugs.Also results shown a significant decreases in the urinary potassium, otherwise plasma sodium levels withinthe normal elevated malady in patients, when compared with healthy control. There were significance resultswith moderately increases levels of the patient serums urea and creatinine, as when correlated with healthycontrol investigations. The current study found that BMI does not differ in patient groups (with cardiacarrest) when compared with the normal healthy control group and each were within the BMI range fornormal weight of a person both in males and females. It was concluded that uses of antihypertensive drugsand NSAIDs lead to lowering aldosterone levels that relates hypertension treatments and inflammatorydiseases.
Keywords: ACEI, Aldosterone, NSAIDs, Potassium, Sodium